Sheath Structure in Oxygen Plasma for Different Presheath Plasma Density - Kaphle, Vikash; Khanal, Raju (Himalayan Physics, 2011)
Zinc oxide films are used as transparent conductive electrode for preparing organic light-emitting devices. In plasma-enhanced vapor deposition oxygen plasma is formed which then react with zinc atoms forming zinc oxide plasma, which is then deposited to the substrate. Hence, the proper understanding of the oxygen plasma-wall interaction is of crucial importance because of its application in plasma depositions. We have studied the sheath structure in oxygen plasma formed in front of an absorbing material wall for different density at the presheath side. We have used a kinetic trajectory simulation model to simulate the oxygen plasma. It has been observed that the sheath structure is highly affected by the plasma density at the presheath side. Hence, the densities of particles reaching the wall can be controlled by adjusting the presheath plasma density which is the key to thin film deposition. Keywords: Plasma; Sheath; Presheath; Quasineutrality; Bohm criterion The Himalayan Physics Vol.1, No.1, May, 2010 Page: 10-13 Uploaded Date: 28 July, 2011